Sodium Hydroxide Treatment Of Waste Rubber Crumb And Its Effects On Properties Of Unsaturated Polyester Composites - Sapuan, S.M.; Mustafa, Nuzaimah; Jawaid, Mohammad; Razali, Nadlene (MDPI AG, 2020)
This study investigated the optimum NaOH concentration treatment for rubber crumbs that improves adhesion between the polymer matrix and rubber filler in rubber polyester composites. The composite was prepared by mixing rubber crumbs from waste rubber gloves with unsaturated polyester matrix. Rubber crumbs were cryogenically ground from waste gloves and treated with 1%, 4%, 7%, and 10% NaOH (by volume). Treatment with 7% and 10% NaOH provides better wettability and hydrophilicity for rubber as it decreases the surface contact angle by approximately 27%. Higher concentration of NaOH intensively etched the rubber and made the surface rougher with more microcracks, providing a larger surface area for greater polyester coverage and holding the rubber firmly. It also induced more functional groups that increased the rubber surface energy and removed the hydrophobic layer on the rubber. These factors strengthened the interfacial rubber-polyester adhesion, as shown by the SEM micrograph of the tensile fracture which the rubber crumbs adhere well to the polyester matrix. The FTIR analysis of rubber treated with higher NaOH concentration showed a higher peak intensity, which demonstrated more polar groups were generated on the rubber surface. More polar groups created further connections to the polar groups in the polyester matrix, thereby enhancing adhesion between the rubber filler and the matrix.